Research on the Time-Dependent Behavior of Uplift Piles in Structured Clay Foundations in Zhanjiang Formation - Yonghui Yang; Tang Bin; Yinchuan Wang; Xingyun Huang; Zuyuan Yu (Applied Sciences)
The structural clay of the Zhanjiang Formation exhibits significant thixotropy, and there are considerable differences in the ultimate bearing capacity of pulled-out piles under different resting times. Using the structural clay from the Zhanjiang Formation as the foundation, direct shear tests on the soil surrounding nine groups of model single piles of different sizes were conducted at various resting times, along with static pullout tests on the pile foundations. The results indicate that the cohesion and internal friction angle of the surrounding soil increase following a logarithmic function with increasing resting time; specifically, the growth rate is rapid in the early resting period and gradually slows down in the later period. A quantitative relationship describing the variation of cohesion and internal friction angle over time was established. The load–displacement curves for single piles at different resting times exhibit a distinct steep drop. The uplift single pile exhibits significant time-dependency, with the ultimate uplift bearing capacity increasing more rapidly in the early stages and gradually stabilizing in the later stages. Under different resting times, for each load level, the maximum side friction resistance of the pile gradually shifts to the middle and lower parts of the pile body, while the ultimate side friction resistance is evenly distributed along the lower part of the pile body, with the side friction resistance of the pile bearing the uplift load. Based on the quantitative relationship of the cohesion and internal friction angle of the surrounding soil around the pile varying with time, a predictive formula for the axial pullout ultimate bearing capacity of a single pile in the Zhanjiang Group structured clay foundation has been established. Using existing pile foundation projects, model experiments were designed to verify the validity of the formula; however, there is a lack of field-scale validation. The research findings can provide a reference for predicting the axial pullout ultimate bearing capacity of single piles in practical engineering applications.